Pengembangan Aplikasi Skrining Kesehatan Mental - Gustiadi, Andri (Jurnal Informasi Kesehatan Indonesia (JIKI), 2024)
Background: Mental health problems in Indonesia, especially among students as a vulnerable group, require serious attention. Mental health surveillance, such as screening, is a preventive and promotive measure to reduce the risk of mental disorders. The utilization of mobile technology is an effective strategy used for rapid and interactive surveillance implementation. The purpose of this study is to develop a mobile application for mental health screening using the Depression Anxiety Stress Scales-21 (DASS-21) instrument. Subjects and Method: The method used in the development of this application is Rapid Application Development (RAD) with the Depression Anxiety Stress Scales-21 (DASS-21) instrument. Researchers took samples using purposive sampling technique, which involved 5 experts (health promotion experts, psychologists, media experts, application experts, surveillance data experts) and 5 student members of UKM-PIKMA youth mental health division as respondents. Results: The application development was carried out through several stages, and succeeded in obtaining an average eligibility score from experts of 91.63% (very feasible) and students of 94.72% (very feasible). The results of the Intraclass Correlation Coefficient (ICC) test showed good reliability with a coefficient of 0.757 from experts and 0.810 from students. This application namely mental care can finally be accessed in Google Play Store. Conclusion: This research successfully developed an application called “Mental Care” with an Android-based operating system. The development of mental health applications is feasible to use to support mental health surveillance activities in students. Keywords: Android, Mental Health Application, RAD, Screening.